A novel mutation in homeobox DNA binding domain of HOXC13 gene underlies pure hair and nail ectodermal dysplasia (ECTD9) in a Pakistani family - Anwar Kamal Khan; Noor Muhammad; Abdul Aziz; Sher Alam Khan; Khadim Shah; Abdul Nasir; Muzammil Ahmad Khan; Saadullah Khan (BMC, 2017)
Abstract Background Pure hair and nail ectodermal dysplasia (PHNED) is a congenital disorder of hair abnormalities and nail dysplasia. Both autosomal recessive and dominant inheritance fashion of PHNED occurs. In literature, to date, five different forms of PHNED have been reported at molecular level, having three genes known and two loci with no gene yet. Methods In this study, a four generations consanguineous family of Pakistani origin with autosomal recessive PHNED was investigated. Affected members exhibited PHNED phenotypes with involvement of complete hair loss and nail dysplasia. To screen for mutation in the genes (HOXC13, KRT74, KRT85), its coding exons and exons-intron boundaries were sequenced. The 3D models of normal and mutated HOXC13 were predicted by using homology modeling. Results Through investigating the family to known loci, the family was mapped to ectodermal dysplasia 9 (ECTD9) loci with genetic address of 12q13.13. Mutation screening revealed a novel missense mutation (c.929A > C; p.Asn310Thr) in homeobox DNA binding domain of HOXC13 gene in affected members of the family. Due to mutation, loss of hydrogen bonding and difference in potential energy occurs, which may resulting in alteration of protein function. Conclusion This is the first mutation reported in homeodomain, while 5th mutation reported in HOXC13 gene causing PHNED.